2020
DOI: 10.1002/pen.25318
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and conducting composites of cobalt ferrite nanorods in a polyaniline matrix

Abstract: Composites of cobalt ferrite nanorods in a polyaniline matrix have been synthesized and characterized by electron microscopy observation, X‐ray diffraction, infrared spectroscopy, thermogravimetric analysis, electrical conductivity, and DC magnetization measurements. The composites were prepared using dodecylbenzenesulphonic acid both as a particle protector and as acid media. In the magnetic experiments, hysteresis loops were observed, revealing ferromagnetism for both particles and composites. The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The absorption maxima peaks at 3428, 3385, and 3329 cm −1 correspond to the vibrations of the N-H bond. 35,57,58 Distinctive peaks corresponding to the stretching vibrations of the vC-H bond can be found at 3298, 3281, 3158 and 3097 cm −1 . The presence of alkyl substituents in the nanohybrids was confirmed by the C-H bond peaks at 2919 and 2867 cm −1 .…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The absorption maxima peaks at 3428, 3385, and 3329 cm −1 correspond to the vibrations of the N-H bond. 35,57,58 Distinctive peaks corresponding to the stretching vibrations of the vC-H bond can be found at 3298, 3281, 3158 and 3097 cm −1 . The presence of alkyl substituents in the nanohybrids was confirmed by the C-H bond peaks at 2919 and 2867 cm −1 .…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Landa et al [ 26 ] introduced CoFe 2 O 4 particles in polyaniline and observed that electrical conductivity was enhanced (reaching the metallic domain), while the remanence and coercive field were slightly diminished due to the polymer phase. Saggion et al [ 27 ] used CoFe 2 O 4 nanorods and incorporated them in the same conductive matrix. Their composites displayed conductivity in the semiconductor domain, whereas the magnetic features of the filler were maintained and the magnetic response of the composite was sensitive to the ferrite amount.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we have studied the influence of the composition on the morphology and physicochemical properties of composite materials based on CoFe 2 O 4 magnetic nanoparticles and different conducting polymers. 19,[25][26][27]31,32 Moreover, the results have been rationalized in terms of the interactions, finding that, in PANI-CoFe 2 O 4 nanocomposites, an indirect exchange mechanism (RKKY-like coupling) between CoFe 2 O 4 MNP and PANI governs the magnetic behaviour of the composites. 27 On the other hand, in the case of PEDOT-CoFe 2 O 4 composites, 19 we found that the nanoparticles appear aggregated in clusters, and that the composite morphology depends on the composition.…”
Section: Introductionmentioning
confidence: 99%